Comparison Study for the Effect of Interleukin -6 and Carbimazole Drug in Rat Thyroid Gland Functions - Razaq, Shaima; Al-Lehibi, Khalid; Alwachi, Sabah (Iraqi Journal of Science, 2023)
Since the inflammatory factor IL-6 known by its critical role in different metabolic reactions in thebody, therefore, this study was designed to detect it is effect in the thyroid gland function byinjecting three groups of rats, the first with IL-6 , the second with carbimazole (antithyroid drug) andthe third with normal saline (Control).The experiment included three groups of rat; each was injectedwith recombinant human interleukin-6 (rhIL-6), Carbimazole, or normal saline (Control). The resultsof experiments showed that both IL-6 and carbimazole caused a decrease in the levels of thyroidhormones (T3 and T4) in animal sera, and a significant decrease in animal body weight, but had noeffect on the liver weight.There was a significant decrease in glucose level in the animals injectedwith carbimazole, while in the IL-6 treated animals there was no change in glucose level. There wasa significant increase in serum level of triglyceride and very low density lipoprotein cholesterol inthe animals treated with IL-6, while in the animals treated with carbimazole, there was no suchchange. Additionally, injection of the animals with IL-6 or carbimazole caused a significant increasein lymphocyte apoptosis of peripheral blood.